Ambivalence, equivocation and the politics of experimental knowledge: A transdisciplinary neuroscience encounter. (October 2014) - Fitzgerald, Des; Littlefield, Melissa M; Knudsen, Kasper J; Tonks, James; Dietz, Martin J
This article is about a transdisciplinary project between the social, human and life sciences, and the felt experiences of the researchers involved. 'Transdisciplinary' and 'interdisciplinary' research-modes have been the subject of much attention lately – especially as they cross boundaries between the social/humanistic and natural sciences. However, there has been less attention, from within science and technology studies, to what it is actually like to participate in such a research-space. This article contributes to that literature through an empirical reflection on the progress of one collaborative and transdisciplinary project: a novel experiment in neuroscientific lie detection, entangling science and technology studies, literary studies, sociology, anthropology, clinical psychology and cognitive neuroscience. Its central argument is twofold: (1) that, in addition to ideal-type tropes of transdisciplinary conciliation or integration, such projects may also be organized around some more subterranean logics of ambivalence, reserve and critique; (2) that an account of the mundane ressentiment of collaboration allows for a more careful attention to the awkward forms of 'experimental politics' that may flow through, and indeed propel, collaborative work more broadly. Building on these claims, the article concludes with a suggestion that such subterranean logics may be indissociable from some forms of collaboration, and it proposes an ethic of 'equivocal speech' as a way to live with and through these kinds of transdisciplinary experiences.